Pengaruh Job Satisfication dan Employee Commitment Akibat Employee Commodification Terhadap Turnover Intention Jurnalis Generasi Z - Iman Indrati (JURISMA : Jurnal Riset Bisnis & Manajemen, 2025)
Turnover intention among Generation Z has been increasing alongside the growing commodification of labor. Unfavorable working conditions, disproportionate pay compared to workload, contract-based employment, lack of job security, and anxiety over termination have driven this generation to seek new opportunities. This study aims to analyze the influence of job satisfaction and employee commitment on turnover intention among Generation Z journalists. A quantitative approach was used with a sample of 110 journalists from the Media Group. The findings reveal that job satisfaction significantly reduces turnover intention. In contrast, employee commitment does not have a direct effect, although a negative relationship between the two was observed. Simultaneously, both variables influence turnover intention. The novelty of this research lies in identifying job satisfaction indicators such as competitive salary, training opportunities, involvement in problem solving, leave entitlements, motivation, SOP evaluation, teamwork, and appropriate job placement. Employee commitment is measured through perceptions of the company as a life asset, trust, and career opportunities. Turnover intention is assessed through new job opportunities, compensation, and personal decisions. The study recommends that companies enhance communication, involve employees in policy-making, and strengthen affective commitment to reduce turnover intention and create a healthier, more productive work environment. Keywords: Employee; Journalist; Job Satisfaction; Commitment; Turnover intention